The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/ol.2015.3312
|View full text |Cite
|
Sign up to set email alerts
|

A novel combination of triple metachronous malignancies of the kidney, oropharynx and prostate: A case report

Abstract: Abstract. Synchronous or metachronous malignancies are a rare event, with an incidence rate that increases with age. The present study reports the case of a 70-year-old Caucasian male who was referred to the outpatient office of the Urology Unit, Sapienza University of Rome (Latina, Italy) due to lower urinary tract symptoms. An abdominal ultrasound investigation was performed that demonstrated the presence of a right renal mass. The patient underwent right radical nephrectomy, which resulted in the definitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Solid tumors comprised 90% of all second malignancies in RCC patients, with the most common second cancers reported in the prostate gland and the digestive and respiratory systems. As shown in Table 1 , in recent years, only five synchronous primary PRAD cases have been reported in RCC patients, with an average age of 68 [ 8 , 9 , 10 , 11 , 12 ]. Most cases (three cases) were diagnosed as RCC of Furhman grade II and PRAD of Gleason score more than 6.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Solid tumors comprised 90% of all second malignancies in RCC patients, with the most common second cancers reported in the prostate gland and the digestive and respiratory systems. As shown in Table 1 , in recent years, only five synchronous primary PRAD cases have been reported in RCC patients, with an average age of 68 [ 8 , 9 , 10 , 11 , 12 ]. Most cases (three cases) were diagnosed as RCC of Furhman grade II and PRAD of Gleason score more than 6.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…This may lead to the development of MPM at some point during the lifetime [ 19 22 ]. Multiple metachronous malignancies are frequently detected in hematological, lung, thyroid, breast, skin, and genitourinary malignancies [ 23 , 24 ]. Liu et al investigated the etiological factors, clinical characteristics, diagnosis, treatment strategies, and prognosis of MPM and demonstrated that curative surgery has a strong impact on long-term prognosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, as PRC is asymptomatic in the early stages ( 47 ) and is an internal disease, it is frequently incidentally detected. In order to confirm the diagnosis method of PRC of those patients, the cases in Table I were further reviewed and the manner in which the subsequent PRC was detected is indicated ( 28 , 29 , 31 , 33 35 , 37 , 38 ) ( Table II ). Of the 9 patients in which PRC was diagnosed, including the present case, PRC was detected by a serum test in 2, incidentally by surgery of the other tumor in 2, by FDG-PET in 2 and by clinical symptoms in 1 (PRC detection in 2 patients was not described).…”
Section: Discussionmentioning
confidence: 99%